Aristotle's "Certain Kind of Multitude". (April 2015) - Cherry, Kevin M.
Political theorists have recently emphasized the popular dimension of Aristotle's political thought, and many have called attention to Aristotle's assertion that certain multitudes should share in the city's deliberations. In this article, I explore the "part of virtue and prudence" Aristotle believes necessary for a multitude to participate in political life. I argue, first, that military service helps citizens develop the "part of virtue" necessary for political participation and, second, that the "part of prudence" Aristotle has in mind is sunesis . I argue, moreover, that military virtue helps citizens acquire sunesis and guides its exercise. Aristotle recognizes the limitations and potential dangers of military virtue and attempts to avoid these, in part by offering a new understanding of military virtue to offset the Spartan. Understanding the "part of virtue and prudence" citizens have helps understand their role in a polity but also points to how those citizens, and their regime, can be improved.